Kontekstualisasi Talak Karena Terpaksa Telaah Kritis Pendapat Empat Madzhab - Mustakim, Ahmad; Muftadi, Kafid (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2025)
This article responds to the issue of the original legal ruling of divorce (ṭalāq) by examining the opinions of scholars from the four Sunni schools of law, which need to be explained comprehensively in order to understand the legal consequences that may arise. The purpose of this article is to provide knowledge by presenting various scholarly opinions from the different schools regarding divorce carried out under coercion. The basic legal ruling of divorce differs among the schools of law: some consider it permissible (mubāḥ), while others regard it as reprehensible (makrūh) if carried out without a valid sharʿī reason. This article also discusses the differences of opinion among scholars concerning divorce under conditions of coercion. The Ḥanafī school considers a divorce to remain valid even if it is pronounced under coercion, whereas the other three schools (Mālikī, Shāfiʿī, and Ḥanbalī) argue that a coerced divorce is invalid. This discussion aims to provide a comprehensive understanding of the concept of divorce in Islam and the dynamics of scholarly thought surrounding it.